2022
DOI: 10.1021/jacs.1c12698
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Oxidation of Single Carbon Nanoparticles: Dependence on the Surface Structure and Probing Real-Time Structural Evolution via Kinetics

Abstract: O2 oxidation and sublimation kinetics for >30 individual nanoparticles (NPs) of five different feedstocks (graphite, graphene oxide, carbon black, diamond, and nano-onion) were measured using single-NP mass spectrometry at temperatures (T NP) in the 1100–2900 K range. It was found that oxidation, studied in the 1200–1600 K range, is highly sensitive to the NP surface structure, with etching efficiencies (EEO2 ) varying by up to 4 orders of magnitude, whereas sublimation rates, significant only for T NP ≥ ∼1700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Preheating had no clear effect on EE O2 at 1500, 1750, or 1800 K. The NP-to-NP variations are expected, particularly for non-preheated NPs, because there would have been NP-to-NP variations in initial shapes and structure (i.e., primary vs aggregate NPs). The variations in initial EE O2 values for preheated NPs was significantly smaller and also much smaller than the variations found for carbon NPs, , where melting is not possible, and the NP feedstocks have very different structures (diamond, graphitic, etc. ).…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…Preheating had no clear effect on EE O2 at 1500, 1750, or 1800 K. The NP-to-NP variations are expected, particularly for non-preheated NPs, because there would have been NP-to-NP variations in initial shapes and structure (i.e., primary vs aggregate NPs). The variations in initial EE O2 values for preheated NPs was significantly smaller and also much smaller than the variations found for carbon NPs, , where melting is not possible, and the NP feedstocks have very different structures (diamond, graphitic, etc. ).…”
Section: Resultsmentioning
confidence: 70%
“…The Si(100) studies also showed that O ads should have mostly desorbed as SiO in our T NP range, maintaining low steady-state oxygen coverage. Our typical P O2 corresponds to ∼154 O 2 collisions/s/nm 2 ; thus, 0.1% sticking would have resulted in adsorption of ∼0.3 O ads /s/nm 2 . If all the O ads desorbed as SiO (g) , the initial mass loss rate would have been ∼8.6 Da/s/nm 2 , corresponding to EE O2 ≈ 5.6 × 10 −2 Da/O 2 collision.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations